POTRET KELOMPOK REMAJA PENGGEMAR DIECAST DI JAKARTA - Jusuf Fadilah; Dina Andriana; Widarti Widarti (Universitas Bina Sarana Informatika, 2018)
Abstract - This study aims to analyze the reasons why a person joins a diecast fan group, to analyze the activities of diecast fan youth groups in Jakarta, to analyze the impact of following diecast fan groups. Data analysis technique used in this research is qualitative data analysis that is, data reduction, presentation (display) data and data verification. The results obtained from the research that the authors do, the authors see there are various reasons behind the Barokah Garage members to join the group of diecast fan teens. Barokah Garage activity is not only gathered, but Barokah Garage routinely performs photography activities diecast toys, social service, hunting together, therefore the impact is not only the body to be healthy because hunting together, the social sense of the teenagers is increasing due to social activities which is routinely implemented.